2018
DOI: 10.1186/s42408-018-0011-y
|View full text |Cite
|
Sign up to set email alerts
|

Forest structure and regeneration responses 15 years after wildfire in a ponderosa pine and mixed-conifer ecotone, Arizona, USA

Abstract: Background: Accelerated vegetation changes are predicted for Southwestern forests due to changing disturbance regimes and climate. The 2001 Leroux Fire burned across a landscape with pre-existing permanent plots during one of the most extreme drought periods over the last few decades, providing a rare opportunity to assess wildfire −drought interactions. The wildfire burned with variable severity across a mountainous transition zone. We took advantage of this opportunity to re-measure plots originally establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…According to the European Forest Fire Information System, Poland ranks third (after Portugal and Spain) in the average annual number of fires and eighth in the area covered by fires (Szczygieł 2012). The role of fires in the formation of the species composition of woody plants, restoration of stands and changes in soil properties have been widely studied (Martìnez-Sánchez et al 1999;González-Pérez et al 2004;Certini 2005;Knicker 2007;Homann et al 2011;Verma and Jayakumar 2012;Barros et al 2018;Stoddard et al 2018). Many studies have also demonstrated either the negative or the positive effects of forest fires on carabid beetle assemblages (Holliday 1991;Beaudry et al 1997;Wikars 1997;Gongalsky et al 2006) and their biomass (Skłodowski 1994).…”
Section: Introductionmentioning
confidence: 99%
“…According to the European Forest Fire Information System, Poland ranks third (after Portugal and Spain) in the average annual number of fires and eighth in the area covered by fires (Szczygieł 2012). The role of fires in the formation of the species composition of woody plants, restoration of stands and changes in soil properties have been widely studied (Martìnez-Sánchez et al 1999;González-Pérez et al 2004;Certini 2005;Knicker 2007;Homann et al 2011;Verma and Jayakumar 2012;Barros et al 2018;Stoddard et al 2018). Many studies have also demonstrated either the negative or the positive effects of forest fires on carabid beetle assemblages (Holliday 1991;Beaudry et al 1997;Wikars 1997;Gongalsky et al 2006) and their biomass (Skłodowski 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Tree regeneration was also roughly 50% absent in studies of dry pine and mixed‐conifer forest on the western side of the Sierra Nevada and the eastern side of the Rocky Mountains, which has a strong rain‐shadow effect analogous to the ESN (Rother and Veblen 2016, Welch et al 2016). Sparse or absent post‐fire tree regeneration has also been widely noted in other semi‐arid pine forests, especially close to the lower treeline or in high‐severity burn patches (Donato et al 2016, Owen et al 2017, Haffey et al 2018, Stoddard et al 2018, Coop et al 2019, Kemp et al 2019). Similarly, tree regeneration in pinyon–juniper woodlands may take decades to over a century to occur following high‐severity fire, especially if shrubs that act as nurse plants are killed (Erdman 1970, Koniak 1985, Romme et al 2009).…”
Section: Discussionmentioning
confidence: 92%
“…Gambel oak and quaking aspen recruits or resprouts occurred both 1 and 2 years post-fire at 100% of plots where they had been present previously, with Gambel oak averaging 10,000 stems ha −1 , and aspen averaging over 5000 stems ha −1 . Research on the Leroux Fire in Arizona, which burned through similar forest types as the Spring Creek Fire, found vigorous aspen response in the first year after fire, but observed that densities declined to below pre-fire levels over the following decade in all burn severity classes (Stoddard et al 2018). While long-term patterns on the Spring Creek Fire will require repeated observations in the years to come, short-term transitions to dominance of these deciduous species are likely to persist without the prevalence of conifer regeneration or heavy ungulate browsing.…”
Section: The Role Of Soil Moisture Temperature and Competing Vegetati...mentioning
confidence: 99%